Teacher Feedback And Students’ Participation in Classroom Interaction - Arsita Wulan Cahyani; Ivorie Rahiema Verandra Asyigah; Ruqoyyah Amilia Andania (STKIP AL HIKMAH SURABAYA, 2024)
This study aims to explore the teacher feedback that use to promote classroom interaction. A descriptive qualitative research approach was utilized, incorporating observations, interviews, and questionnaires for data collection. The participants in this study two English teachers of senior high school. The result revealed that the EFL teacher generally employs evaluative feedback to acknowledge and encourage students, making it the most common sort of verbal feedback in the transcript. This technique promotes a positive learning environment and encourages students to participate in the session actively. To improve the learning experience, teachers should balance the use of evaluative, interactive, and corrective feedback. Increasing interactive feedback by asking open-ended questions and promoting student discussion might help students grasp more deeply. More detailed corrective feedback, as well as opportunities for self- and peer-correction, can increase learners' awareness and accountability. Regular evaluation of feedback practices, as well as incorporating student feedback, helps ensure that the methods utilized fit the different requirements of students.